1981
DOI: 10.2323/jgam.27.145
|View full text |Cite
|
Sign up to set email alerts
|

Microbial characteristics of ruminal fluid from feedlot bloat beef cattle.

Abstract: Rumen samples from bloating steers had volatile fatty acids (VFA) concentrations high in acetate and low in propionate so that the acetate/ propionate ratio was consistently higher in bloating animals than in healthy ones. The ruminal pH values in bloated steers were compatible with those in healthy steers. Ammonia concentrations were higher in bloated steers than in healthy ones. There were no essential differences in the rates of gas production in vitro by rumen fluid between bloated and healthy steers. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, the ratio of acetic to propanoic acid was significantly (p < 0.05) higher in the foam itself than in layers B, C, or D of foaming and non-foaming storages. This may be significant, as Sakauchi and Hoshino (1981) found that rumen fluid from bloated steers had a higher acetic to propanoic acid ratio than rumen fluid from healthy steers, suggesting some similarities in the mechanisms of foam formation in deep-pit storages and bloat in feedlot cattle.…”
Section: Resultsmentioning
confidence: 95%
“…However, the ratio of acetic to propanoic acid was significantly (p < 0.05) higher in the foam itself than in layers B, C, or D of foaming and non-foaming storages. This may be significant, as Sakauchi and Hoshino (1981) found that rumen fluid from bloated steers had a higher acetic to propanoic acid ratio than rumen fluid from healthy steers, suggesting some similarities in the mechanisms of foam formation in deep-pit storages and bloat in feedlot cattle.…”
Section: Resultsmentioning
confidence: 95%
“…rumen fill and particle size reduction, and those which have been implicated in the aetiology of bloat, i.e. degradation of plant leaf and release of chloroplasts (Howarth et al 1982;Majak et al 1985), fermentation (Clarke & Reid, 1974), and volatile fatty acid (VFA) production (Sukachi & Hoshino, 1981).…”
mentioning
confidence: 99%
“…As mentioned above, the rumen foam agent and foam stabilizer can only originate from feeds and rumen microorganisms. Numerous studies have found that rumen bloat occurs only in some animals, even when fed the same feed ( 32 , 33 ). The reason for this phenomenon may be related to individual differences in the structural composition of rumen microbes, suggesting that rumen microbes play an important role in the development of rumen bloat.…”
Section: Pathogenesis Of Feedlot Bloatmentioning
confidence: 99%